Results of a phase I trial to assess the safety of macitentan in combination with temozolomide for the treatment of recurrent glioblastoma. Issue 1 (2nd October 2021) - Weathers, Shiao-Pei; Rood-Breithaupt, Julie; de Groot, John; Thomas, Gail; Manfrini, Marianna; Penas-Prado, Marta; Puduvalli, Vinay K; Zwingelstein, Christian; Yung, W K Alfred
Abstract: Background: There is an urgent need for additional therapies to treat recurrent glioblastoma (GBM). Preclinical studies suggest that high dose macitentan, an oral dual endothelin receptor antagonist, enhances the cytotoxic effects of temozolomide (TMZ) in GBM, improving survival. This phase I trial investigated the maximum tolerated dose of macitentan combined with TMZ in patients with recurrent GBM and assessed the safety and tolerability of high dose macitentan in these patients (NCT01499251). Methods: Adults with recurrent GBM received ascending doses of macitentan from 30 mg once daily concomitantly with TMZ. Safety and tolerability were assessed in addition to exploratory efficacy and pharmacokinetic endpoints. An ancillary study examined biomarker expression following macitentan treatment prior to surgical resection of recurrent GBM. Results: Thirty-eight patients with recurrent GBM were administered macitentan doses up to 300 mg once daily; no dose-limiting toxicities were observed, and a maximum tolerated dose was not determined. All patients experienced at least one treatment-emergent adverse event (TEAE), the majority associated with GBM or TMZ treatment. TEAEs related to macitentan and TMZ were reported for 16 (42.1%) and 26 (68.4%) patients, respectively, with no serious macitentan-related TEAEs. Macitentan concentrations increased with dose, with no plateau in exposure. Substantial heterogeneity was observed in the expression of efficacy biomarkers within tumors. The Kaplan-Meier estimate of median overall survival across all dose groups was 9.4 (95% CI 8.5, 13.4) months. Conclusion: High-dose macitentan was well tolerated in recurrent GBM patients concomitantly receiving TMZ. TEAEs were consistent with those seen in patients receiving either drug individually.